THE FACTORS THAT AFFECTING FIRM VALUE OF BASIC MATERIALS COMPANIES - Natalia, Natalia (International Journal of Application on Economics and Business, 2025)
The research was carried out to empirically test the influence of leverage, managerial ownership, institutional ownership, efficiency, and firm size on the firm value of the basic materials companies listed on the Indonesia Stock Exchange in 2020-2022. The research design applied was descriptive statistics, and the sample selection technique used was the purposive sampling method. The number of samples used was 33 samples from 11 companies using multiple linear regression analysis techniques. The data in the research were processed through the EViews 12 program. This research obtained results where leverage and efficiency had an insignificant positive effect on firm value, managerial ownership had an insignificant negative effect on firm value, institutional ownership had a significant positive effect on firm value, and company size had a significant negative effect on firm value.